Absolute oxygen-guided radiation therapy improves tumor control in three preclinical tumor models - Gertsenshteyn, Inna; Epel, Boris; Giurcanu, Mihai; Barth, Eugene; Lukens, John; Hall, Kayla; Martinez, Jenipher Flores; Grana, Mellissa; Maggio, Matthew; Miller, Richard C.; Sundramoorthy, Subramanian V.; Krzykawska-Serda, Martyna; et al. (Frontiers in Medicine, 2023)
Background: Clinical attempts to find benefit from specifically targeting and boosting resistant hypoxic tumor subvolumes have been promising but inconclusive. While a first preclinical murine tumor type showed significant improved control with hypoxic tumor boosts, a more thorough investigation of efficacy from boosting hypoxic subvolumes defined by electron paramagnetic resonance oxygen imaging (EPROI) is necessary. The present study confirms improved hypoxic tumor control results in three different tumor types using a clonogenic assay and explores potential confounding experimental conditions. Materials and Methods: Three murine tumor models were used for multi-modal imaging and radiotherapy: MCa-4 mammary adenocarcinomas, SCC7 squamous cell carcinomas, and FSa fibrosarcomas. Registered T2-weighted MRI tumor boundaries, hypoxia defined by EPROI as pO2 ≤ 10 mmHg, and X-RAD 225Cx CT boost boundaries were obtained for all animals. 13 Gy boosts were directed to hypoxic or equal-integral-volume oxygenated tumor regions and monitored for regrowth. Kaplan-Meier survival analysis was used to assess local tumor control probability (LTCP). The Cox proportional hazards model was used to assess the hazard ratio of tumor progression of Hypoxic Boost vs Oxygenated Boost for each tumor type controlling for experimental confounding This is a provisional file, not the final typeset article variables such as EPROI radiofrequency, tumor volume, hypoxic fraction, and delay between imaging and radiation treatment. Results: An overall significant increase in LTCP from Hypoxia Boost vs Oxygenated Boost treatments was observed in the full group of three tumor types (p<0.0001). The effects of tumor volume and hypoxic fraction on LTCP were dependent on tumor type. The delay between imaging and boost treatments did not have a significant effect on LTCP for all tumor types. Conclusion: This study confirms that EPROI locates resistant tumor hypoxic regions for radiation boost, increasing clonogenic LTCP, with potential enhanced therapeutic index in three tumor types. Preclinical absolute EPROI may provide correction for clinical hypoxia images using additional clinical physiologic MRI.